Clinical analysis of 173 pediatric patients with antibody-mediated autoimmune diseases of the central nervous system: a single-center cohort study - Kang, Qingyun; Liao, Hongmei; Yang, Liming; Fang, Hongjun; Ning, Zeshu; Liao, Caishi; Gan, Siyi; Wu, Liwen (Frontiers in Immunology, 2023)
Background Antibody-mediated disorders of the central nervous system (CNS) have seen a gradual rise in their incidence and prevalence. This retrospective observational study aimed to investigate the clinical characteristics and short-term prognosis of children with antibody-mediated CNS autoimmune diseases at Hunan Children’s Hospital. Methods We collected the clinical data of 173 pediatric patients diagnosed with antibody-mediated CNS autoimmune diseases between June 2014 and June 2021 and analyzed their demographics, clinical features, imaging and laboratory data, treatment, and prognosis. Results A total of 187 patients tested positive for anti-neural antibodies and 173 patients were finally diagnosed with antibody-mediated CNS autoimmune diseases after excluding the 14 false-positive cases through clinical phenotypic evaluation and follow-up of treatment outcomes. Of the 173 confirmed patients, 97 (56.06%) were positive for anti-NMDA-receptor antibody, 48 (27.75%) for anti-MOG antibody, 30 (17.34%) for anti-GFAP antibody, 5 (2.89%) for anti-CASPR2 antibody, 3 (1.73%) for anti-AQP4 antibody, 2 (1.16%) for anti-GABABR antibody, and 1 (0.58%) for anti-LGI1antibody. Anti-NMDAR encephalitis was the most commonly seen among the patients, followed by MOG antibody-associated disorders and autoimmune GFAP astrocytopathy. Psycho-behavioral abnormalities, seizures, involuntary movements, and speech disorder were the most common clinical presentations of anti-NMDAR encephalitis, while fever, headache, and disturbance of consciousness or vision were the most seen among patients with MOG antibody-associated disorders or autoimmune GFAP astrocytopathy. The coexistence of multiple anti-neural antibodies was detected in 13 patients, among which 6 cases had coexistent anti-NMDAR and anti-MOG antibodies (including 1 case with anti-GFAP antibody also), 3 cases had coexistent anti-NMDAR and anti-GFAP antibodies, 3 cases had coexistent anti-MOG and anti-GFAP antibodies, 1 case had coexistent anti-NMDAR and anti-CASPR2 antibodies, and 1 case had coexistent anti-GABABR and anti-CASPR2 antibodies. All the survivors were followed up for at least 12 months; 137 recovered completely, 33 had varying sequelae, and 3 died; 22 had one or more relapses. Conclusion Antibody-mediated CNS autoimmune diseases occur in children of all ages. Most such pediatric patients have a good response to immunotherapy. Despite the low mortality rate, some survivors have a non-negligible risk of developing relapses.